Using effective and adequate IT tools for developing teachers' skills - Smyrnova-Trybulska, Eugenia; Morze, N.; Pavlova, T.; Kommers, P.; Sekret, I. (Inderscience Publishers, 2017)
This article describes preliminary results of the implementation of Work Package 4 'Selection and testing new IT tools' within the framework of the international research network IRNet (www.irnet.us.edu.pl) and by researchers from partner institutions from Portugal, Poland, Ukraine, Russia, Czech Republic, the Netherlands and Turkey. These results relate to an analysis and study of a category of IT tools for making presentations and didactic videos, for formative continuous assessment (real-life and online), remote collaborative work and virtual meetings, virtual rooms, learning management systems for educational process support, online tutoring and social media. The package period has been divided into main stages: 1-5.